21st century geography a reference handbook - Stoltman, Joseph P. (Thousand Oaks, Calif. London SAGE, 2012)
Using 80 mini-chapters, this title highlights the most important topics, issues, questions and debates any student obtaining a degree in this field ought to have mastered for effectiveness in the 21st century.
Includes bibliographical references and index.
Keywords: Geography